Signora Volpe. Series 1 [videorecording (DVD)] - Cuperman, Rachel; Griffiths, Sally (Acorn, 2022)
Top British spy Sylvia Fox is in Italy for her niece's wedding when the groom goes missing, leaving a dead body behind him. Sylvia solves the mystery and falls in love with Italy, and with a crumbling old house on a hillside. Disillusioned with her job and longing to reconnect with her family, Sylvia decides to stay on and start a new life in the little town of Panicale. But trouble has a habit of seeking Sylvia out and she finds herself tackling a fresh mystery every week and in the process, becoming increasingly close to handsome local cop Giovanni Riva.